O processo administrativo sancionador das agências reguladoras de serviços públicos - Eid, Isabella Martinho (2018)
Several public services which are indispensable to the Brazilian society are regulated by special autarchies known as regulatory agencies, due to a sequence of structural changes that affected the Brazilian state during the decade of 1990, usually referred by the legal doctrine as The Reform of the State Apparatus. These figures reflect a model imported from foreign legislation, in special from United States of America. These entities are, in great part of situations, responsible for the promotion, in the exercise of their regulatory functions, of punitive processes and the application of administrative penalties to public services concessionaires. Therefore, it is necessary to analyze the objectives of the punitive processes in general and the specific characteristics that condition its legality within the framework of public service regulatory agencies as well. This exam is important to enhance the fact that the absence of theses aspects defile the main function of these autarchies, provoking serious damages not only to the rights of the referred concessionaires, but to all juridical pretensions comprehended in the corresponding economical universe, especially the services users. This distortion violates the main reason of existence of these public organisms: the improvement of the quality of the public services, instructed by technical and specialized knowledge, and the harmonization of all juridical relations formed between the several agents affected by the corresponding economical sector